The construction of three C–P bonds of P-stereogenic tertiary phosphines containing (l)-menthyl. Issue 15 (2nd July 2020) - Ye, Jing-Jing; Yan, Bing-Xia; Wang, Ji-Ping; Wen, Jing-Hong; Zhang, Yu; Qiu, Mao-Ran; Li, Qiang; Zhao, Chang-Qiu
Abstract : A wide range of R P or S P -(l )-menthyl-containing SPOs were prepared via the reaction of 1, 1′-bi(2-naphthol) derived phosphonite with a metallic reagent with excellent yield and dr. Abstract : A wide range of R P or S P -(l )-menthyl-containing SPOs were prepared via the reaction of 1, 1′-bi(2-naphthol) derived phosphonite with a metallic reagent with excellent yield and dr. The formation of the P -stereogenic center was controlled by the binaphthol moiety and the products were stereospecifically converted into TPOs under phase transfer conditions.